Physical constrains and productivity in the future Arctic Ocean - Slagstad, Dag; Wassmann, Paul F. J.; Ellingsen, Ingrid (Frontiers in Marine Science, 2015)
Todays physical oceanography and primary and secondary production was investigated for the entire Arctic Ocean with the physical-biologically coupled SINMOD model. To obtain indications on the effect of climate change in the 21th century the magnitude of change, and where and when these may take place SINMOD was forced with down-scaled climate trajectories of the International Panel of Climate Change with the A1B climate scenario which appears to predict an average global atmospheric temperature increase of 3.5 to 4 °C at the end of this century. It is projected that some surface water features of the physical oceanography in the Arctic Ocean and adjacent regions will change considerably. The largest changes will occur along the continuous domains of Pacific and in particular regarding Atlantic Water advection and the inflow shelves. Withdrawal of ice will increase primary production, but stratification will persist or, for the most, get stronger as a function of ice-melt and thermal warming along the inflow shelves. Thus the nutrient dependent new and harvestable production will not increase proportionally with increasing photosynthetic active radiation. The greatest increases in primary production are found along the Eurasian perimeter of the Arctic Ocean (up to 40 g C m-2 y-1) and in particular in the northern Barents and Kara Seas (40-80 g C m-2 y-1) where less ice-cover implies less Arctic Water and thus less stratification. Along the shelf break engirdling the Arctic Ocean upwelling and vertical mixing supplies nutrients to the euphotic zone when ice-cover withdraws northwards. The production of Arctic copepods along the Eurasian perimeter of the Arctic Ocean will increase significantly by the end of this century (2-4 g C m-2 y-1). Primary and secondary production will decrease along the southern sections of the continuous advection domains of Pacific and Atlantic Water due to increasing thermal stratification. In the central Arctic Ocean primary production will not increase much due to stratification-induced nutrient limitation.